Effects of Sawdust and Rice husk Additives on Physical Properties of Ceramic Filter (Journal of University of Babylon for Engineering Sciences, 2017)
Two processes were employed for forming, specifically,  slip casting and semi-dry press were used to manufacture ceramic filters from local raw materials, red clay and combustible materials  (sawdust and rice husk). Different proportions of additives were used as pores forming agents to create porosity in ceramic filter. Dried filters  were fired at temperature to 1000°C.  It was found that the forming technique and additives have great effect on the physical properties of the produced ceramic filters. The slip casting technique was more suitable procedure for producing a porous ceramic filter. As well as, porosity increased as percentage of the combustible materials increased.